Studies of Cell Cycle-associated Proteins in a Case of Giant Cell Granuloma of Mandible - Xu, MD, PhD, Bo; Balos, MD, Lucia; Goodloe, MD, Samuel; Krabill, MD, Keith; Chmiel, Jr, DDS, Ronald; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2009)
Central Giant Cell Granuloma (CGCG) is a localized benign osteolytic lesion with variably aggressive nature. Due to the rarity of this disease, only a few studies with a limited number of cases have been reported, the results of which are controversial. Hence, there is not much data on the possible mechanisms underlying its aggressive biological behavior. In our study, immunohistochemistry was performed on a 50-year old female diagnosed with a giant cell granuloma of the mandible. We attempted to examine the expression profile and cellular distribution of cell cycle-associated proteins: cyclin D1, p53, PCNA, MIB-1 and facor XIIIa. Our results demonstrated that high-level expression of cyclin D1 was predominant in the nuclei of 85% of giant cells whereas cyclin D1 staining was noticed in only 20% of mononuclear cells. Expression of PCNA and MIB-1, on the other hand, was observed in 70% and 40% of mononuclear cells respectively, with less than 10% positive staining present in the giant cells. P53 protein did not appear to be over-expressed in either mononuclear or giant cells, and factor XIIIa was detected only in isolated stromal fibroblasts. These results support the hypothesis that over-expression of cyclin D1 in giant cells may play a role in the pathogenesis of CGCG, and the differential expression pattern of cyclin D1 and PCNA may be involved in the formation of multinucleated giant cells. [N A J Med Sci. 2009;2(2):48-50.]